Thermal behaviour and the prospect spread of an invasive benthic top predator onto the Euro‐Arctic shelves. Issue 9 (18th February 2015) - Christiansen, Jørgen S.; Sparboe, Maria; Sæther, Bjørn‐S.; Siikavuopio, Sten I.; MacIsaac, Hugh
Abstract Aim A focal task for invasion biology is to identify the environmental variables and biological traits that set and underpin realised and potential habitats of invasive species. Ecophysiology provides powerful empirical knowledge that connects theory with natural phenomena and may improve the accuracy of species distribution modelling. We used the introduced Kamchatka red king crab Paralithodes camtschaticus of the Barents Sea as a prime case to show how thermal behaviour may drive the spreading of a marine invader in context of ocean warming. Finally, we discuss the conceivable consequences for a poleward spread of invasive top predators on native marine biota, conservation and management policies. Location Barents Sea, Euro‐Arctic shelves, Northeast Atlantic. Methods We used novel and non‐manipulative tests which allowed adult red king crab to freely select and monitor ambient temperature in situ across a < 1–14 °C gradient by means of a temperature data storage tag attached to the carapace. Results Adult red king crab, irrespective of body size, maturation stage and nutritional state, (1) displays clear behavioural thermoregulation in a hetero‐thermal environment and, (2) conclusively selects temperatures in the coldest end of a gradient and avoids temperatures > 4 °C. The final thermal preferendum matches completely present day Arctic shelf temperatures north and east in the Barents Sea. Main conclusions This is the first published study on the thermal behaviour of a marine invasive top predator. Our tests and the concurrent realised habitat north‐east of Kola Peninsula suggest that the introduced red king crab is capable of invading the Euro‐Arctic shelves in less than three decades. We argue that current management practices of the introduced red king crab compromise Arctic biodiversity and conservation and, to counteract further spreading, we recommend free fisheries on this species across its entire distributional area in the Northeast Atlantic.